Factors That Influence Students' Learning Interest in the Subject of Islamic Cultural History at the Tarbiyah Islamiyah Tsanawiyah Madrasah in Jambi City - Siti Alvira DesmaPutri; M Yahuda (Journal of Educational Studies, 2026)
Students’ learning interest plays a crucial role in determining the effectiveness of the learning process and academic achievement. However, preliminary observations at Madrasah Tsanawiyah Tarbiyah Islamiyah Jambi City indicated that students exhibited a relatively low level of interest in Islamic Cultural History (ICH) learning. This study aimed to explore the factors influencing students’ learning interest in ICH. Employing a qualitative approach with a descriptive design, the study involved 19 students from Class VIII A as research participants. Data were collected through classroom observations, semi-structured interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing and verification. The findings revealed that students’ learning interest in ICH was shaped by both internal and external factors. Internal factors comprised low learning motivation, unfavorable perceptions of the subject matter, and limited attention and concentration during classroom activities. Meanwhile, external factors included the limited use of varied instructional methods, inadequate learning media, teachers’ constraints in managing instructional time, and a learning environment that was not fully conducive to student engagement. These factors collectively contributed to students’ low participation and enthusiasm in the learning process. The study highlights the importance of implementing innovative pedagogical approaches, utilizing interactive learning media, and creating a supportive learning environment to foster students’ interest and engagement in Islamic Cultural History learning.